Gene Editing in Plants - Padhi, S K (International Journal of Psychosocial Rehabilitation, 2025)
Gene editing or genome editing is a type of genetic engineering in which the DNA is introduced, deleted, modified or replaced into the genome of a living organism. It is the deliberate alteration of a selected DNA sequence in a living cell. In this, a strand of DNA is cut by using the molecular scissors at a specific point and the broken DNA strands are fixed together with the help of DNA ligase by naturally existing cellular repair mechanism. It was first accomplished by Herbert Boyer and Stanley Cohen in 1972. It is an important technology for making changes in DNA, which includes the changes in physical traits such as eye color or risk of any disease. Genome / gene editing using Engineered Endonuclease (GEEN) systems have been well established over the fields of plant biotechnology. Till now, gene editing have been implicated in various different plants such as Arabidopsis including the main crops like rice, wheat and maize and some less important crops such as strawberry, cucumber, etc. To improve the safety of food, the research in plant biology aims at improving the yield of crops and various other factors such as biotic and abiotic stress, along with the enhancement in the nutritional content of food